Pastoral do Migrante: relações e mediações: Ana Cristina Arantes Nasser e Sidnei Marco Dornelas. São Paulo: CEM; Loyola, 2008. 367p. - Pereira, José Carlos Alves (TRAVESSIA - revista do migrante, 2009)
[...]